Quality of vision, patient satisfaction and long-term visual function after bilateral implantation of a low addition multifocal intraocular lens - Pedrotti, Emilio; Mastropasqua, Rodolfo; Bonetto, Jacopo; Demasi, Christian; Aiello, Francesco; Nucci, Carlo; Mariotti, Cesare; Marchini, Giorgio (International ophthalmology, 2018)
Purpose The aim of the current study was to compare the quality of vision, contrast sensitivity and patient satisfaction with a biaspheric, segmented, rotationally asymmetric IOL (Lentis Comfort LS-313 MF 15-Oculentis GmbH, Berlin, Germany) as opposed to those of a monofocal IOL. Methods This prospective single-blind comparative study included two groups of patients affected by bilateral senile cataract who underwent lens extraction and IOL implantation. The first group received a bilateral implantation of a monofocal IOL, and the second group received a bilateral implantation of the Comfort IOL. Twelve months after surgery uncorrected and corrected visual acuity at different distances (30, 50, 70 cm and 4 m), defocus curve and contrast sensitivity were assessed. Patient’s satisfaction and spectacle independence were evaluated by mean of the NEI RQL-42 questionnaire. Results No significant differences were found between the groups in terms of near vision. The group of patients implanted with a Comfort IOL obtained the best results at intermediate distances (50 and 70 cm P < .001). Both groups showed an excellent uncorrected distance visual acuity (4 m). No statistically significant differences were found in terms of corrected near, intermediate and distance visual acuity. Concerning contrast sensitivity, no statistically significant differences between the groups were observed at any cycles per degree. The NEI RQL-42 questionnaire showed statistically significant differences between the group for “near vision” ( P = .015), “dependence on correction” ( P = .048) and “suboptimal correction” ( P < .001) subscales. Conclusion Our findings indicated that the Comfort IOL +1.5 D provides a good intermediate spectacle independence together with a high quality of vision, with a low amount of subjective symptoms and a contrast sensitivity similar to those obtained with a monofocal IOL.